Syariah compliant hotel: The concept and practices / Nur’Hidayah Che Ahmat ... [et al.] - Che Ahmat, Nur’ Hidayah; Ahmad Ridzuan, Ahmad Hidayat; Din, Norrina; Zainol, Noorliza; Razali, Mohamad Azli (2015)
The current tourism trends boost up the demand for and supply of Islamic hospitality services. It is believe that the successful stories of Islamic financing is one of the driving factors of Syariah Compli-ant hotels besides the increasing number of Arab and Muslim trav-ellers and their high purchasing power. Howbeit, detailed guide-lines need to be introduced in constructing this concept since there are diverse opinions and contradiction in understanding the concept and practices among the hotel operators and Syariah scholars. Re-cent studies confirmed that currently there is no comprehensive standardization being introduced yet and hotel operators came out with their own interpretation of compliant strategies. Some are overly exposed their Syariah Compliant concept through marketing strategy and concentrating too much on to be the pioneer without knowing the part and parcel of the true Syariah Compliant. With that, this study will be discussing on the awareness and acceptance level of the customers on Syariah Compliant hotel concept and practices.